Modular design for constructing narrowband deep-blue multiresonant thermally activated delayed fluorescent emitters for efficient organic light emitting diodes - Naveen, Kenkera Rayappa; Lee, Hyuna; Seung, Lee Hyun; Jung, Young Hun; Keshavananda Prabhu, C.P.; Muruganantham, Subramanian; Kwon, Jang Hyuk (Chemical engineering journal (Lausanne, Switzerland : 1996), 2023)
[Display omitted] •Deep Blue MR-TADF emitters were designed by incorporating rigid DOBNA into MR skeletons.•Both emitters possess narrowband deep blue emission with FWHM of 19 nm.•Small ΔEST (0.05 eV) and high PLQY are realized in the emitters.•MR-TADF OLEDs demonstrate high EQEs (>30 %) with CIE y coordinate below ≤ 0.07. The simultaneous achievement of high efficiency and deep blue narrowband emission in multi resonant thermally activated delayed fluorescence (MR-TADF) materials are crucial and challenging. Herein we report two deep blue MR-TADF emitters, namely, TPD4PA and tBu-TPD4PA, using double boron, three nitrogen and two oxygen atoms. The design is based on amalgamating the high charge transfer (CT) characteristic moiety into MR-type fragments towards efficient MR-TADF emitters with improved CT characteristics. Both the materials show deep blue photo luminescent emissions of ∼450 nm with a high photoluminescence quantum yield (PLQY) of ∼90 %. These materials showed very small singlet–triplet gap (≤0.06 eV) and a high rate of reverse intersystem crossing of ∼2.5 × 105 s−1. The TADF devices based on TPD4PA and tBu-TPD4PA showed maximum external quantum efficiencies of 30.7 and 32.5 %, respectively. Furthermore, both devices exhibited narrow band deep blue emissions and corresponding CIE y coordinates 0.06 and 0.07, which match near NTSC and BT2020 blue color requirements.